Implementasi Kurikulum ISMUBA (Islam Muhammadiyah Bahasa Arab) Dalam IMTAK dan IPTEK di SMA Muhammadiyah Pangkalpinang - Zidane Romadhonie (Magister Pendidikan Agama Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study examines the use of the ISMUBA (Islam Muhammadiyah Arabic Language) curriculum at SMA Muhammadiyah Pangkalpinang. Regarding the challenges encountered by the education sector in the age of globalization and substantial technical advancements, The implementation of a curriculum approach is essential in order to effectively address the advancements in globalization, democratic society, and the proactive response to the progress of information and science. The implementation of a curriculum is crucial in education to foster a productive, efficient, and innovative learning experience. The objective of this study was to assess the teacher's comprehension of the ISMUBA curriculum in the context of the teaching and learning process. In Islam, religious knowledge (IMTAK) and general science (science and technology) are not considered independent entities, as they both originate from the same source, which is Allah SWT. Religious knowledge is direct knowledge bestowed by Allah SWT. Al-Islam Kemuhammadiyahan Arabic Education (ISMUBA) is a distinctive feature and benefit exclusive to Muhammadiyah schools and madrasahs. The advancement of Muhammadiyah education is structured through an integrated and holistic system of modern Islamic education.